Eletronic Health Records using Blockchain Technology - Conceição, Arlindo F. da; Silva, Flavio S. Correa da; Rocha, Vladimir; Locoro, Angela; Barguil, João Marcos M. (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain), 2018)
Data privacy refers to ensuring that users keep control over access to information, whereas data accessibility refers to ensuring that information access is unconstrained. Conflicts between privacy and accessibility of data are natural to occur, and healthcare is a domain in which they are particularly relevant. In the present article, we discuss how blockchain technology, and smart contracts, could help in some typical scenarios related to data access, data management and data interoperability for the specific healthcare domain. We then propose the implementation of a large-scale information architecture to access Electronic Health Records (EHRs) based on Smart Contracts as information mediators. Our main contribution is the framing of data privacy and accessibility issues in healthcare and the proposal of an integrated blockchain based architecture.